Pemberdayaan Lansia Melalui Senam Lansia Untuk Pencegahan Nyeri Rematik di Dusun 3 Desa Suka Sari Kecamatan Kabawetan - A, Arif Syamsulhadi; Annisa, Annisa; Redjangies, Bunga; Febriani, Yola; Fitriani, Viola Dwi Nurul; Putri, Yesi (Jurnal Dehasen Untuk Negeri, 2026)
Rheumatic pain is a common health problem experienced by the elderly due to degenerative processes in the musculoskeletal system. This condition impacts the quality of life and independence of the elderly. Empowering the elderly through exercise is a non-pharmacological effort that can be implemented sustainably in the community. This activity aims to improve the elderly's ability to perform exercise as an effort to prevent rheumatic pain. The method used was a quasi-experimental design with a pretest and posttest. The results showed a decrease in pain complaints, increased joint flexibility, and improvements in the physical and psychological conditions of the elderly. Empowering the elderly through exercise has proven effective as a promotive and preventive strategy in preventing rheumatic pain